Back Cover: Remote Regulation of Membrane Channel Activity by Site‐Specific Localization of Lanthanide‐Doped Upconversion Nanocrystals (Angew. Chem. Int. Ed. 11/2017). Issue 11 (15th February 2017) - Ai, Xiangzhao; Lyu, Linna; Zhang, Yang; Tang, Yanxia; Mu, Jing; Liu, Fang; Zhou, Yixi; Zuo, Zhenghong; Liu, Gang; Xing, Bengang
Abstract : Spatiotemporal regulation of membrane channel activity in living systems has been achieved by irradiation with near‐IR light ( λ =808 nm), as reported by B. Xing, G. Liu, and co‐workers in their Communication onpage 3031 ff. Metabolic glycan biosynthesis is used to attach lanthanide‐doped upconversion nanocrystals (UCNs) to the cell surface through copper‐free click cyclization. Cation influx can be controlled by irradiation and membrane‐associated activities manipulated in living cells and zebrafish.